The new low shear viscosimeter LS300 for determination of viscosities of Newtonian and non-Newtonian fluids - Ruef, Peter; Gehm, Jutta; Gehm, Lothar; Schmidt, Claudia; Pöschl, Johannes; Kuß, Navina (General physiology and biophysics, 2014)
The low shear viscometer LS300 permits measurements of viscosity with the same precision of the LS30 but is now fully controlled by the windows based software. That allows to determine viscosity at several shear rates and to establish flow curves enabling determination of the viscosity of non-Newtonian fluids. The viscosity of whole blood of ten adults was determined via flow curves approximated by Casson. The sensitivity of the LS300 was evaluated by determining the viscosity of water at rising temperatures and by establishing flow curves of ten specimen of the same blood sample.
Gesehen am 28.09.2020